2021
DOI: 10.1088/1755-1315/911/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Classifying cassava (Manihot esculenta Crantz.) clones based on principal component analysis of specific characters for use as selection criteria

Abstract: There is an abundance of cassava (Manihot esculenta Crantz.) genetic resources in Indonesia, and the local accessions are inseparable from the community of Indonesia. Several of the cultivars have cultural significance and over time have been bred for specific uses and products. The specific use and combination of traits encourages the use of local cultivars or aims for genetic improvement of the local cultivars. The objective of this study was to measure character variability and to categorize cassava clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to Table 3, our study found that 94% (except G59, G61, G62, and G64) of the evaluated accessions had little to no root constriction, 34.4% (G1, G3, G4, G5, G6, G10, G11, G15, G22, G23, G30, G33, G38, G41, G43, G44, G45, G46, G47, G57, G60, and G64) had white or cream external root color, 5% (G23, G36, and G40) had yellow root pulp color, 31.3% (G2, G9, G12, G13, G15, G24, G28, G29, G33, G34, G35, G36, G48, G49, G50, G52, G53, G55, G59, and G63) had white or cream root cortex, and 46.9% (G7, G9, G11, G13, G16, G20, G25, G26, G29, G32, G35, G37, G39, G40, G41, G42, G43, G45, G46, G48, G49, G50, G51, G53, G54, G55, G56, G57, G58, and G61) had ease of removing the root cortex. Phenotypic characterization and evaluation could make the management and the use of several gene banks more efcient [34,35]. Hence, the characterization and evaluation of plant genetic resources indicate the procedures used to assess, classify, distinguish, identify, avoid duplication, and efciently utilize accessions.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 3, our study found that 94% (except G59, G61, G62, and G64) of the evaluated accessions had little to no root constriction, 34.4% (G1, G3, G4, G5, G6, G10, G11, G15, G22, G23, G30, G33, G38, G41, G43, G44, G45, G46, G47, G57, G60, and G64) had white or cream external root color, 5% (G23, G36, and G40) had yellow root pulp color, 31.3% (G2, G9, G12, G13, G15, G24, G28, G29, G33, G34, G35, G36, G48, G49, G50, G52, G53, G55, G59, and G63) had white or cream root cortex, and 46.9% (G7, G9, G11, G13, G16, G20, G25, G26, G29, G32, G35, G37, G39, G40, G41, G42, G43, G45, G46, G48, G49, G50, G51, G53, G54, G55, G56, G57, G58, and G61) had ease of removing the root cortex. Phenotypic characterization and evaluation could make the management and the use of several gene banks more efcient [34,35]. Hence, the characterization and evaluation of plant genetic resources indicate the procedures used to assess, classify, distinguish, identify, avoid duplication, and efciently utilize accessions.…”
Section: Resultsmentioning
confidence: 99%
“…The repeated material is the control from which the diversity of experimental errors is obtained while the tested clones are not repeated [13]. Many breeding studies have used augmented design due to limited planting material or a large number of materials tested such as chickpea [14], cassava [15], soybean [16] cowpea [17], wheat [18], lablab [19], and also garlic [20,21].…”
Section: Introductionmentioning
confidence: 99%